In Search of New Rationality (II) - Šliogeris, Arvydas (Problemos, 1976)
The second part of the paper discusses the Marcusean conception of the new attitude of man towards reality determined by Herbert Marcuse as “a new rationality” in contrast to the scientific-instrumental, technological and thus repressive way of mastering reality. The revived capability of the so-called “negative thinking”, i.e., such mental structures which act as a pure negation of the dominating repressive universe of technological and linguistic systems reigning in the modem industrial society is regarded by Marcuse to be a presupposition of “the new rationality”. The article reveals the metaphysical character of the Marcusean concept of negation based on the idealistic interpretation of the relationship between the structure of cognition and the socio-economic structures. The author criticises from the Marxist point of view the concept of the new rationality disclosing the Utopian character of the whole socio-philosophical doctrine of Herbert Marcuse.